A preliminary study of ice core chronology at Dome Fuji Station, Antarctica - Watanabe, Okitsugu; Fujii, Yoshiyuki; Motoyama, Hideaki; Furukawa, Teruo; Shoji, Hitoshi; Enomoto, Hiroyuki; Kameda, Takao; Narita, Hideki; Naruse, Renji; Hondoh, Takeo; Fujita, Shuji; Mae, Shinji; et al.
A 112．59 m-deep ice core was drilled at Dome Fuji Station by a JARE-34 party in 1993 when a pilot hole was prepared for a deep core drilling operation．A preliminary examination was made for ice core chronology by two signals： one electric conductivity peaks measured in the home laboratory and the other field observation results obtained by JARE-36 party on the deeper part of the core. The electric conductivity peak analyses suggest the same 5 volcanic eruptions, in 1464 AD, 1259 AD, 865 AD, 639 AD and 346 BC, reported for the ice core of Byrd Camp, Antarctica．Field observations for ECM and crystal size distributions suggest that the period 374 m depth level corresponds to the end of Wisconsin ice period The results suggest that accumulation rate at Dome Fuji Station is between 2.5 and 3.O cm of water equivalent/year, and the end of Wisconsin-Holocene Transition will be found between depths of 340 and 400 m．The depth-age curves for the core at Dome Fuji Station are obtained from the surface （at present） to 400 m （at 12000 years BP）. application/pdf journal article